Propuesta de un sistema tratamiento de aguas residuales para la empresa EIS Eléctricos, Ingeniería y Servicios S.A.S. (2020)
The purpose of this project was the development of a proposal for the implementation of a water treatment system for the company EIS SAS in order to create a solution to the final discharge that is based on compliance with parameters according to regulations 0631 / 2015 for disposal in the sewer. Initially, the company's diagnosis was made from the study of industrial processes to identify the pollutants involved in the effluent contamination; A review of water consumption from 2015 to 2019 was carried out immediately, emphasizing the consumption of the last period; The proposals implemented in the company to reduce the pollutant load were also identified, in this case, the grease trap. To conclude this objective, a characterization was carried out with an external laboratory to show which parameters were outside the established values.